A case of welder’s lung with end-stage pulmonary fibrosis - Baur, Xaver; Abraham, Jerrold L. (Pneumologie, 2023)
Background Welding, performed regularly by more than a million workers worldwide, is associated with exposures to irritative, fibrogenic and carcinogenic fumes and gases.Methods and Results We present the case of a welder who had worked under extremely poor hygiene conditions for nearly 20 years and had developed end-stage lung fibrosis, finally requiring lung transplantation. Detailed histopathology and scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS) analyses of his lungs showed advanced interstitial fibrosis and dust deposits in the lungs and in peribronchial lymph nodes containing welding type bodies, Fe, Si (silica), Ti (titanium), SiAl (aluminum silicates), Fe with Cr (Steel), and Zr (Zirkonium).Conclusion In the absence of a systemic disorder and the failure to meet the criteria for diagnosis of idiopathic pulmonary fibrosis (IPF), these findings suggest welder’s lung fibrosis as the most likely diagnosis.
Keywords: Schweißerlungenfibrose; Histopathologie; Rasterelektonenmikroskopie; Energiedisperse Röntgenspektroskopie; Lungenfunktion